Pengaruh Penggunaan Media Pembelajaran Pada Mata Pelajaran Matematika terhadap Keaktifan Belajar Peserta Didik di SMP Negeri 1 Parmonangan Tahun Pembelajaran 2023/2024 - Betty Lusiana Debataraja; Robinhot Sihombing; Erika Christine Panggabean; Justice ZZ Panggabean; Ruslan Juliana Pardosi (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
The aim of this research is to determine the positive and significant influence of the use of learning media in mathematics subjects on the learning activity of students at SMP Negeri 1 Parmonangan for the 2023/2024 academic year. The method used in this research is quantitative with an inferential statistical approach. The population is all class IX students at SMP Negeri 1 Parmonangan in 2024 totaling 68 people and a sample of 44 people was determined, namely 20% of the total population using random sampling techniques. Data was collected using a positive closed questionnaire with 30 items. The results of data analysis show that learning media has a positive and significant effect on students' active learning at SMP Negeri 1 Parmonangan. Test the analysis requirements in this research using the normality test which obtained the Asymp value. signature. (2-tailed) is 0.200, meaning it is greater than 0.05 (0.200 > 0.05) so it can be concluded that the research data is normally distributed. The results of the correlation test show that there is a positive relationship between variable Apart from that, the significant relationship test obtained a value of tcount= 0.629 > ttable(a=0.05, dk=n-2=42)= 2.021, thus there is a significant relationship between variable X and variable Y. The hypothesis was tested through a regression equation test, obtained the regression equation Y ̂=5.255+0.773X and the regression coefficient of determination test (r2) = 39.5%. Testing the hypothesis using the F test obtained Fcount > Ftable, namely 27.470 > 4.08. Thus Ha is accepted and H0 is rejected. So it can be concluded that learning media has a positive and significant effect on the active learning of class XI students at SMP Negeri 1 Parmonangan in 2024.